Implementation of The STEM Learning Model Using Math City MAP (MCM) in Improving Creative and Critical Mathematical Thinking Ability - Risnawati, Risnawati; Sudiyanto, Sudiyanto; Winarni, Retno (Universitas Sebelas Maret, 2024)
There is a need to summarize the result of STEM reachers findings, especially to improve mathematical creatives thinking and mathematical critical thinking skills. This research also synthetisizes relevant studies from various sources include: Google Scholar, Directory Open Access Journal (DOAJ), Semantik Scholar and Education Resources Information Center (ERIC) from 2015 to 2022.The result of the research show that the STEM learning models has a positive and significant influence on increasing critical thonking skills and students’ mathematical creativity. Various descriptions of research characteristics such as sample sizw, level of education, and years of education can be examined further for further research. The intergration of STEM learning models can be used by educators to facilitate students with various project-based taks and problem solving. It is hoped that the use of the Math City map application will be able to motivate students to have joyfull and meaningfull mathematics learning.In this students are required to have critical and creatives mathematical thinkings skills. The results of this research contribute to knowledge for educators and research regardib=ng how STEM should be applied in mathematics lesson.